REGULATION OF EXPORT ACTIVITIES OF SMALL BUSINESS IN THE REPUBLIC OF UZBEKISTAN (World Bulletin of Management and Law, 2023)
In this article are discussed the innovativeness of small business, the need to clearly define the size of a small and medium-sized business as a recipient of support in export activities..